Literaturni ili kulturologichni sravnenia? (Colloquia Comparativa Litterarum, 2025)
Roads and Trails of the Europeanism in the Balkans. In honor of the 50th anniversary since the Institute for Balkan Studies & Center of Thracology foundation.